A report of farmer field days at the multilocation trial sites in Mbarara and Ngetta zonal agricultural research and development institutes in Uganda - Lukuyu, Ben A.; Mudde, Barnabas; Wentaro, Amos; Obong, Samson; Tugume, Gershom; Ahumuza, Ronnie; Businge, Martha (International Livestock Research Institute, 2024)
The dairy value chain is a primary focus of the International Livestock Research Institute (ILRI) through the CGIAR Sustainable Animal Productivity for Livelihoods, Nutrition, and Gender Inclusion (SAPLING) Initiative. This initiative aims to enhance the livestock sector in targeted countries by promoting productivity, resilience, equity, and sustainability. One of its key objectives is to boost livestock productivity, thereby improving the livelihoods of farmers. A vital approach to achieving this is by enhancing farmers' access to and utilization of high-quality feeds and forages.